Acute Kidney Injury in Patients with Diabetic Ketoacidosis at National Institute of Child Health - Syeda Sadia Ahmed, Mashal Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To determine the frequency of acute kidney injury (AKI) in patients with diabetic Ketoacidosis at National Institute of Child Health (NICH). Materials and Methods: Totally 80 patients who were enrolled. Demographics data were noted. Five ml venous blood sample and urine sample were collected from of each child in aseptic conditions in sterilized container and sent to laboratory of the hospital for random blood sugar (RBS), serum urea, serum creatinine, serum electrolytes (Na, K, Ph,) complete blood count (CBC, hemoglobin (Hb), white blood cells (WBC), platelets count, arterial blood gas (ABG), and ketones. All were drawn at the time of admission and after 24 hours. All children were catheterized at time of admission to monitor urine output which is part of DKA protocol and was recorded at 6, 12, 24 hours. AKI were labelled according to KDIGO classification as stage I, II, III depending upon rise in serum creatinine from baseline or according to urine output at 6, 12, 24 hours. All the demographic details and duration of diabetes mellitus and DKA and its treatment were recorded on a predesigned data collection proforma. Results: Out of 80 patients, 44.3% were male and 55.7% were female with mean age of 9.63± 3.34 years. 67% of the patients were aged 7.1-14 years, followed by 27% patients were aged 1-7 years and only 5.7% patients were aged of 14.1-18 years. The mean Duration of hospital stay was 6.88±1.45 days. The Mean Hb and WBCs, and Platelets level were 12.13±1.9 g/l, 16.37±7.97 and 348836.3±140355.4 respectively. The mean PH of all the enrolled patients was found 7.08±0.14 and mean Bicarbonate was 7.54±3.37mmol/L. The mean RBS at admission time and after 24-hour treatment were 403.7±95.42 mg/dl and 266.7±65.1 mg/dl respectively. The mean Serum Urea at admission time and after 24-hour treatment were 36.6±28.9 mg/dl and 36.9±23.5 mg/dl respectively. And the mean serum creatinine (mg/dl) at admission time and after 24-hour treatment were 0.75±0.58 and 0.76±0.55 mg/dl respectively. The mean electrolytes (Na, K, Ph) at admission time and after 24 hours were 138.4±7.0 mmol/l and 139.1±4.0 mmol/l, 4.0±0.83 mg/dl and 4.88±4.83 mg/dl, 19.2±30.7 mg/dl and 16.1±22.0 mg/dl respectively. Frequency of AKI was 31.8% and patients needed for peritoneal dialysis were 3.4%. Practical implication: In our study it was find out that AKI is a common complication in patients with Diabetic ketoacidosis. So this study will help the clinical practioner to also treat the patients for acute kidney injury that will provide early recovery from all the symptom of acute kidney injury. Conclusion: AKI is a common complication in children who are admitted for DKA and clinical practitioner should take precautionary parameter to avoid such complication. Keywords: Acute Kidney Injury, Diabetic Ketoacidosis, Children, DM, DM Type-1, child health, Frequency, NICH